Perubahan Perilaku Masyarakat Buang Air Besar Sembarangan (BABS) Menuju Hidup Bersih dan Sehat - Siti Tenricapa; Renny Nurhasana; Noviyati V. Sidabutar; Rini Kurniawati; Alfred R. Januar Nabal; R. Bayu Sanjaya (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
Open defecation is still carried out in several locations in Jakarta, especially in slum settlements as a result of uncontrolled migration flows that are not accompanied by the readiness and availability of adequate housing. Basically, this behavior is a way of fulfilling the biological need to defecate. Individual ways to fulfill it are influenced by external factors and individual internal factors, which can shape behavior in a positive or negative direction. These ways are strongly influenced by the determinants of behavior. This study aims to raise facts on the ground which show that there are differences in reactions to interventions carried out in an effort to change open defecation behavior that occurs in marginalized Jakarta communities towards clean and healthy living behavior (PHBS). In addition, to find the driving factors that influence the success of behavior change. This research took place in two residential locations, namely RT.15/RW.07 and RT.01/RW.03, North Tanjung Duren Village, Grogol Petamburan District, West Jakarta Administrative City. The research method is descriptive qualitative. Research factors are reinforcing, predisposing, and enabling factors. The results of this study identified differences in the factors driving behavior change in the two research locations. At the location of RT.01/RW.03, there are external stimuli and agents of change (reinforcing factor), cohesiveness in society (predisposing factor), empowerment/independence (enabling factor). In the location of RT.15/RW.07, there are external stimuli and agents of change, while the other two factors are not owned and instead become quite basic differentiators when compared to the first location and there are obstacles in the form of a culture of poverty among the residents of RT.15/RW. 07, which relies more on government assistance, has also colored the contrast in people's awareness of clean and healthy living behavior.